An evaluation on microleakage and gap width of different dentin bonding agents in high copper amalgam restorations - Ghavam-Nasiri M. Associate Professor; Malek-Nejad F. Assistant Professor; Rohani A. Dentist; Akbari M. Dentist (Tehran University of Medical Sciences, 2003)
Statement of Problem: A lot of efforts have been made to create a complete adaptation between tooth"nand amalgam restorations."nPurpose: The aim of this study was to evaluate microleakage and interfacial micromorphology of"namalgam restorations lined with dentin adhesives, namely One Coat Bond, Syntac, Excite and Copalite,"nas liners."nMaterials and Methods: 144 intact human canine teeth were selected. Then class V cavities, with"nenamel and dentinal margins, were prepared on each of them. Cavities were lined with different dentin"nbonding systems (Syntac, One Coat Bond and Excite) according to the manufacturer's instructions and"nrestored with Oralloy and Cinalloy, non gamma 2 spherical amalgams and Aristaloy a non gamma 2"nAdmixed alloy. Copalite was used in the group, served as controls. After thirty days storage in synthetic"nsaliva at 37°c, the specimens were thermocycled in saliva (4000 cycles). The degree of microleakage was"nassessed by means of basic fushin dye penetration and recorded. The gap width was evaluated with"nScanning Electron Microscope. Pearson and %2 tests were used to analyze the results."nResults: None of the systems, tested in this study, eliminated microleakage completely, Pearson's"ncorrelation coefficient showed a positive correlation between gap and microleakage (P<0/05).Statistical"nsignificant differences were revealed among the liners regarding gap and microleakage (P<0.05)."nOne Coat Bond and Syntac appeared to leak less than other groups. The gap width by One Coat Bond"nand Syntac were respectively 0.35 and 0.3 urn in dentine, 0.2 and 0.1 in enamel. Excite and copalite gap"nwidth in dentine and enamel were 1,3-1.36 urn and 0.3-0.6, respectively. The type of amalgam did not"nhave any effect in the degree of microleakage and gap width (P>0/05)."nConclusion: One Coat Bond and Syntac, comparing to Excite and Copalite, showed less microleakage"nand gap width.